PENGARUH SESAR CIMANDIRI TERHADAP MORFOLOGI DAERAH PADALARANG - Haryanto, Iyan; Sunardi, Edy (Bulletin of Scientific Contribution, 2014)
Cimandiri Fault is a regional fault that stretching from Pelabuhanratu (Sukabumi) to end up in the complex area of Mt. Tangkubanprahu – Mt. Burangrang (Subang - Northward of Bandung). Regional fault has been widely studied, but there are differences of opinion, especially regarding the type of shift.This study aimed to examine all aspects relating to Cimandiri Fault, especially along the segment Tagokapu-Cibogo (Padalarang-Citatah), so that can be known about the type of the fault. Steps and methods of research, among others, to analyze the landscape through satelite image, make observations, descriptions and measurement of geological structure elements, data processing by program using "dip" and "Paleostress" softwares. Cimandiri fault lines along the segment Tagokapu-Cibogo, can be recognized from various aspects, among others, from the aspect of geomorphology characterized by differences in the shape and elevation of the hills; from stratigraphical aspects there are contact between rock formations of different ages; from fold structure aspects there are found standing upright rock layers; and from the aspect of fault outcrop, there were indications that the fault is generally associated with horizontal fault. From the results of the analysis showed that the lineament of Cimandiri Fault along Tagokapu-Cibogo segment, controlled by a reverse fault and normal faults that formed in different tectonic period.